Study on subsurface damage mechanism of gallium nitride in nano-grinding. (15th June 2021) - Zhang, Chaoyue; Dong, Zhigang; Yuan, Song; Guo, Xiaoguang; Kang, Renke; Guo, Dongming
Abstract: Molecular Dynamics simulations were carried out to study the formation mechanism of subsurface damage during the process of nano-grinding of gallium nitride (GaN). The effects of grinding depths and speeds on the temperature, the radial distribution function, phase transition, dislocation and the damage layer were systematically investigated. The results showed that quantities of interstitial atom, vacancy defects, atomic clusters, "U"-shaped half dislocation loops and Phase transition atoms exist in the subsurface layer. Additionally, the temperature, dislocation density and the number of phase transition atoms are positively related with the grinding depths, and then resulting in the quality of subsurface decreases with the increase of grinding depths. Although the damage layer is more sensitive to the grinding depth, when the speed increases from 25 m/s to 50 m/s, the above parameters also increase slightly, thus the subsurface quality decreases. As the speed continues to grow, these parameters gradually decrease due to the sharp decrease in processing time, and the quality of subsurface layer improves. This study provides an insight into the subsurface damage mechanism for the low-damage processing of GaN.